De Persona a Pessoa: o reconhecimento da dignidade do nascituro perante a ordem jurídica brasileira - CARNEIRO FILHO, Humberto João (2012)
This dissertation intends to analyze the attribution of the juridical category of “person” to the unborn child in the context of the juridical-philosophical formulation of meanings attributed to the term person, from the Roman tradition until the context of the crisis of legal security by codification in which the dignity is juridically chosen as a value of the human person. In Roman law, the concept of the person (persona) was not endowed from the abstract, how it was attributed by the Pandectistic of the 19th century, but embraced the human being concretely in his multiple dimensions, inclusively considering itself as such the unborn child, to which was guaranteed the rights in view of his birth. In regard of axiom conceptus pro iam nato habetur, based in the roman treatment given to the unborn, emerged two interpretations: one, more faithful to the Justinian tradition, which recognizes the concrete reality of the unborn child and equates him to the already born, and the other, abstract, sustained by the Pandectistic and based on the thoughts of Savigny, which considers the parity between the unborn and the born simply a mere fiction. This latter interpretation influenced the elaboration of many civil codes like the German and the Brazilian Code of 1916, both of which determined that the natural personhood can be attributed only when the child is born alive. The idea of personhood while a simple legal attribution withdraws itself from the philosophical tradition that considers the person in his ontological aspects, a fact that deserves to be recognized as primary in the juridical planning. The principle of human dignity, incorporated in the Brazilian Constitution of 1988 as the foundation of the Republic, serves as an indication of an ‘ethical personalism’ which reflects itself in personal rights, providing elements to enlarge the semantic content of the juridical concept of person, recognizing the personal dignity of the unborn child, as done in the ‘Pact of San Jose, Costa Rica’ (American Convention on Human Rights), to singularize the juridical personhood as a right and the unborn child as a person. Keywords: